'Nước Việtnam là Quê Hương Của Tôi:' historical, political and sociocultural implications of the Vietnamese-American researcher in sport for development.". Issue 4 (4th July 2021) - Dao, Michael
ABSTRACT: Using autoethnography I draw on my experiences conducting fieldwork in Vietnam on Sport for Development (SfD) to explore the historical, political, and sociocultural vulnerabilities of the Vietnamese-American researcher in SfD. In doing so, I narrate and revisit the past of my parents and how their memories influenced my research and identity. Of central concern in this paper is how historical and biographical portrayals (Mills, 1959) of being Vietnamese-American ultimately affected the SfD research process and experience. To be clear this paper is not about SfD, per se, instead, it gives insight about research done with and in communities that are close to one's history and biography. That is, I am a Vietnamese person born in America who 'returned' to the country of his family to conduct research. To that end, I write inspired by and connect to the written memoirs from the Vietnamese diaspora. I argue complicating SfD research from points of history and biography offers insight into how a researcher 'going home' negotiates the historical, sociocultural and political implications of their research. Thus, by illustrating the complex relationship of being a Vietnamese-American researcher in Vietnam through autoethnography, I write with the intent to speak to SfD research, while specifically speaking to a larger Vietnamese-researcher audience.